1986
DOI: 10.1017/s0043174500067023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Johnsongrass (Sorghum halepense) Density on Sugarcane (Saccharum officinarum) Yield

Abstract: The effects of johnsongrass [Sorghum halepense(L.) Pers. # SORHA] infestations were determined during a 2-yr study on sugarcane (Saccharum officinarumL. ‘CP-65-357’) yield. Both cane and sugar yields were lower (36 and 31%, respectively) in plots heavily infested with johnsongrass than in weed-free plots. Sugarcane yields were inversely influenced by johnsongrass equivalents (the sum of the values obtained by multiplying the number of clumps by their corresponding importance value for each plot). In 1983, both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…In addition, D. saccharalis infestations in experimental rice plots located within 1.25 km of noncrop sampling transects in Jackson County represented Ͼ99% of stem borer infestations in JulyÐAugust 2007 (Beuzelin 2011). In the Louisiana sugarcane agroecosystem, Bynum et al (1938) and Ali et al (1986) concluded that johnsongrass only played a minor role in D. saccharalis population build-up and overwintering. These observations suggest that noncrop hosts might contribute less to D. saccharalis populations than to E. loftini populations.…”
Section: Saccharalis Infestations In Noncrop Hostsmentioning
confidence: 99%
“…In addition, D. saccharalis infestations in experimental rice plots located within 1.25 km of noncrop sampling transects in Jackson County represented Ͼ99% of stem borer infestations in JulyÐAugust 2007 (Beuzelin 2011). In the Louisiana sugarcane agroecosystem, Bynum et al (1938) and Ali et al (1986) concluded that johnsongrass only played a minor role in D. saccharalis population build-up and overwintering. These observations suggest that noncrop hosts might contribute less to D. saccharalis populations than to E. loftini populations.…”
Section: Saccharalis Infestations In Noncrop Hostsmentioning
confidence: 99%
“…Like many agronomic crops, sugarcane is most sus ceptible to weed interference during the early stages of the growing season (first 8 to 10 wk after emergence) (1,3). Under the Louisiana culture of sugarcane, this period occurs in the spring following a period of winter dormancy.…”
Section: Introductionmentioning
confidence: 99%
“…Season-long johnsongrass [Sorghum halepense (L.) Pers.] competition has reduced sugar yields approximately 50% when compared with an untreated control (2,14).…”
Section: Resultsmentioning
confidence: 98%